The Massacres at Mt. Halla : Sixty Years of Truth Seeking in South Korea - Kim, Hun Joon, 1975- (Book collections on Project MUSE., 2014)
In The Massacres at Mt. Halla, Hun Joon Kim presents a compelling story of state violence, human rights advocacy, and transitional justice in South Korea since 1947. The "Jeju 4.3 events" were a series of armed uprisings and counterinsurgency actions that occurred between 1947 and 1954 in the rugged landscape around Mt. Halla in Jeju Province, South Korea. The counterinsurgency strategy was extremely brutal, involving mass arrests and detentions, forced relocations, torture, indiscriminate killings, and many large-scale massacres of civilians. The conflict resulted in an estimated thirty thousand deaths, about 10 percent of the total population of Jeju Province in 1947. News of this enormous loss of life was carefully suppressed until the success of the 1987 June Democracy Movement. -- Publisher description